Pengaruh Kompetensi Sumber Daya Manusia Dan Disiplin Kerja Terhadap Kinerja Pegawai Dalam Meningkatkan Motivasi Kerja Sebagai Variabel Intervening Pada Kantor Badan Kepegawaian Dan Pengembangan Sumber Daya (BKPSDM) Kabupaten Agam - Yollanda Septi; Mondra Neldi; Olandari Mulyadi (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The purpose of this study was to determine how much influence Human Resource Competence and Work Discipline have on Employee Performance with Work Motivation as an Intervening Variable at the Office of the Human Resources Development and Personnel Agency (BKPSDM) of Agam Regency. The data analysis method used a questionnaire, with a sample of 3 respondents. The data analysis method used was SEM. The population and sample of this study were employees of the Office of the Human Resources Development and Personnel Agency (BKPSDM) of Agam Regency. Based on the results of the study, it shows that there is a positive and significant influence between Human Resource Competence on Work Motivation. There is a positive and significant influence between Work Discipline on Work Motivation. There is a negative and insignificant influence between Human Resource Competence on Employee Performance. There is a negative and insignificant influence between Work Discipline on Employee Performance. There is a negative and insignificant influence between Work Motivation on Employee Performance. Work Motivation does not mediate Human Resource Competence on Employee Performance. Work Motivation does not mediate Work Discipline on Employee Performance.